Strategic Planning and Human Capital Plan In PT Recycled Paper Hub - Novie Nurliadi Pratiwi; Rhian Indradewa; Tantri Yanuar Syah; Unggul Kustiawan (Dinasti International Journal of Digital Business Management, 2024)
Recycled Paper Hub is a business unit mainly focus in processing recycled paper sorted from local collector who also act as supplier such as waste paper collected from traditional market, ex-packaging collected from home industry and household waste, etc. Recycled Paper Hub primary goal is to participate in the sustainable business by contributing to the economy of the surrounding community along with a commitment to maintaining a green environment. In order to achieve this goals, Recycled Paper Hub conduct business development strategy which include financial planning and projection. This study uses quantitative research methotds. Data collection technique used literature studies, interviews, and observations. Strategic planning was carried out until the long-term stage, according to the business strategy and lean business canvas model. Human capital planning was carried out with the stages of goals and objectives, corporate culture and values, organizational structure, human capital planning, and human capital cost projections.